(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
The ’punk attitude’ that is basic to punk music and culture is hard to define. I argue that it can be more fully appreciated through a comparison with features of, and motivations behind, existentialist philosophy and literature: anti-institutionalism, nihilism, creative outputs and processes that are constantly challenging, and authentic belonging.